2020
DOI: 10.1002/anie.202000209
|View full text |Cite|
|
Sign up to set email alerts
|

Squaramides and Ureas: A Flexible Approach to Polymerase‐Compatible Nucleic Acid Assembly

Abstract: Joining oligonucleotides together (ligation) is a powerful means of retrieving information from the nanoscale. To recover this information, the linkages created must be compatible with polymerases. However, enzymatic ligation is restrictive and current chemical ligation methods lack flexibility. Herein, a versatile ligation platform based on the formation of urea and squaramide artificial backbones from minimally modified 3′‐ and 5′‐amino oligonucleotides is described. One‐pot ligation gives a urea linkage wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…A combinatorial approach for the discovery of splint-templated chemical ligations has been reported to identify DNA-compatible reactions to ligate terminally functionalised ONs [57]. Moreover, the generation of artificial backbone mimics has been shown for bridging 5 0 -S-phosphorothioester linkages (Ps) [58], PA [59][60][61][62], AM [61], urea [63], SQAM [63], TL1 [64] and TL3 [61]. Indeed, copper-catalysed azide-alkyne cycloaddition (CuAAC) to form TL3 was reported for the assembly of whole genes [12,65] and long RNA [9,10] from azide and alkyne modified shorter ONs.…”
Section: Nucleic Acid Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…A combinatorial approach for the discovery of splint-templated chemical ligations has been reported to identify DNA-compatible reactions to ligate terminally functionalised ONs [57]. Moreover, the generation of artificial backbone mimics has been shown for bridging 5 0 -S-phosphorothioester linkages (Ps) [58], PA [59][60][61][62], AM [61], urea [63], SQAM [63], TL1 [64] and TL3 [61]. Indeed, copper-catalysed azide-alkyne cycloaddition (CuAAC) to form TL3 was reported for the assembly of whole genes [12,65] and long RNA [9,10] from azide and alkyne modified shorter ONs.…”
Section: Nucleic Acid Formationmentioning
confidence: 99%
“…Similarly, phosphoramidate backbones can be read by DNA and RNA polymerases [ 59 , 61 ], and translated by ribosomes [ 60 ], and introduction of PA-modified genes can lead to the expression of their associated genetic information in bacteria [ 13 ]. Apart from gene synthesis, artificial backbones such as TL2, [ 31 ] urea [ 63 ] and SQAM [ 63 ] were reported as components of modified primers in PCR. In the case of SQAM, in situ template assembly by target-templated SQAM formation was utilised for RNA detection [ 63 ].…”
Section: Synthetic Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…In general, replication-competent artificial DNA backbones can be used for gene synthesis, , sequencing, or nucleic acid detection . A detailed study revealed several molecular characteristics of artificial backbones that are required for compatibility with DNA polymerases during replication .…”
Section: Introductionmentioning
confidence: 99%
“…A detailed study revealed several molecular characteristics of artificial backbones that are required for compatibility with DNA polymerases during replication . Such polymerase compatible artificial backbones comprise 5′- S -phosphorothioesters, phosphorothioates, disulfides, boranophosphates, phosphoramidates, ,, amides, , ureas, squaramides, and triazoles. ,,, Among these, the triazole linkage (TL) represents a powerful and versatile chemical moiety that can be readily formed by the Cu I -catalyzed azide–alkyne cycloaddition (CuAAC) reaction, resulting in 1,4-disubstituted 1,2,3-triazoles . Examples include TL 1 , TL 4 , TL 5 , and TL 6 (Figure ).…”
Section: Introductionmentioning
confidence: 99%